ANALYSIS OF BUSINESS POLICY STRATEGIES ON CHICKEN WILLIAM MSMES IN BANDUNG CITY - Nurianputri, Awfa Azka; Aldina, Aurellia Thania; Ayurizki, Nourani; Abiyyu, Muhammad Refi; Jaya, Fadi Nurrayhan (Univesitas Muhammadiyah Tangerang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) significantly contribute to Indonesia's economic growth, especially in the Food & Beverage (F&B) sector, which represents 75% of MSMEs in Bandung City as of 2023. This study examines the business strategies of Chicken William MSME through qualitative methods, including interviews, FGDs, and secondary data. Using PESTEL, Porter’s Five Forces, and SWOT analyses, the study identifies challenges and opportunities. Findings highlight that product innovation, operational optimization, digital marketing, halal certification subsidies, and partner collaborations can enhance competitiveness. These strategies are also applicable to other MSMEs in the competitive F&B sector.